Pendekatan Post Modern dalam Studi Islam dan Studi Agama - Ahmad, Upi Sopiah (Lembaga Yasin AlSys, 2022)
After humans go through modern times, humans go through a post-modern life order with models and methods of free life in all aspects of life which in Islam is called postmodernism where traditional values are associated with the postmodernism phase, besides that they reject what is called intellectual education. West technology industrialization as well as the globalization of information. After the presence of postmodern postmodernism, humans are required to make adjustments to the situation where the thought of Islamic studies is adapted to postmodernism methods, which indirectly invites us to assume questions about pluralism, skepticism of traditional orthodoxy, the media is the central dynamic, the figure of postmodernism is more of a philosopher. rather than anthropologists, because they are considered to have failed to connect socio-political ideas and changes in religious fundamental thinking. if we examine that the sociocultural approach is more dominant in the study of postmodernism towards Islamic studies. The Islamic solution to the existence of religious plurality is to recognize the differences and identities of each religion which is called lakum dinukum waliyadin, there are two understandings in relation to pluralism, First Global theology, secondly transcendent unity of Religion. The postmodernism method is a fact of human expertise in creating theoretical treasures within a certain time, on the other hand Islam offers Supra postmodernism for its people where sunatullah is considered a necessity. Currently, not a few Muslim scholars use Western concepts, either directly or just being influenced. Even though quite a number of Muslim scholars have contributed to the development of post-modern thought, if there is a separation between religion and religious thought, it is certain that they will be influenced by relativism, especially postmodernism. in Islamic studies.